Development and analysis of a high refractive index liquid phase Si3N4 slurry for mask stereolithography. Issue 1 (1st January 2022) - Wu, Xiangquan; Xu, Chunjie; Zhang, Zhongming
Abstract: Ceramic mask stereolithography additive manufacturing technology has the abilities of fast and accurate printing complex and personalized ceramic parts. However, since the ultraviolet light is strongly blocked by the ceramic particles in the slurry during exposure, the slurry with high refractive index ceramic particles has low cure depth, and serious light scattering. This investigation developed a curable silicon nitride slurry with a high refractive index liquid phase, which significantly reduced the refractive index difference between the liquid phase and the silicon nitride ceramic particles. The high refractive index acrylate monomer and solvent were chosen to increase the cure depth while ensuring the curing accuracy. Compared with the slurry whose liquid phase was pure HDDA, the addition of OPPEA and ACMO in the liquid phase showed a better refractive index increasing effect and the strongest cure depth and dimensional accuracy improvement. POE was verified as a suitable non-reactive high refractive solvent. The composition of 20 wt% OPPEA, 10 wt% ACMO, 40 wt% HDDA, and 30 wt% POE were optimized as the high refractive index liquid phase for 40 vol% solid phase silicon nitride slurry. A finite element analysis model of silicon nitride slurry was established, and the distribution of ultraviolet light intensity in silicon nitride slurry with high refractive index liquid phase was numerically simulated.